The Effect of Horizontal Communication, Vertical Communication and Diagonal Communication on Employee Work Morale at the Sub-district Office, Rantau Utara - Rosenni Nursetia Lingga; Bayu Eko Broto; Abd Halim (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
This study aims to determine the Effect of Horizontal Communication, Vertical Communication and Diagonal Communication on Employee Morale at the North Rantau Sub-district Office, both partially and simultaneously. The population in this study is employees at the North Rantau Sub-district Office, the study period is from January to July 2023, The determination of sample techniques uses the opinions of 30 people and the analysis methods used are descriptive analysis methods, multiple linear regression analysis, and hypothesis testing, with a variable value of Horizontal Communication calculated at 3,237 while t table 1,703 (tcount > from ttabel) with a sig value of 0.003 smaller than the alpha value of 0.05. Then the value of the Vertical Communication variable is calculated at 3.081 while t table is 1.703 (tcount > from ttabel) with a sig of 0.005 smaller than the alpha value of 0.05. Meanwhile, for the Diagonal Communication variable, the calculation value is 2.907 while the ttabel is 1.703 (t calculate > from the ttabel) with a sig of 0.007 smaller than the alpha value of 0.05. The results of simultaneous hypothesis testing (F test) showed that Horizontal Communication (X1), Vertical Communication (X2) and Diagonal Communication (X3) had a positive and significant effect on employee morale at the North Rantau Sub-district Office, with a calculated value of 9.178 while f table 2.76 (f count is greater than thef tabel). The test results of the Coefficient of determination (R2) can be seen that the Adjusted R square value of 0.458 or 45.8% shows that Horizontal Communication, Vertical Communication and Diagonal Communication against Employee Morale at the North Rantau Sub-district Office of 54.2%